Guidelines for safe automation of chemical processes (CCPS guidelines series., 2017)
This book provides designers and operators of chemical process facilities with a general philosophy and approach to safe automation, including independent layers of safety. An expanded edition, this book includes a revision of original concepts as well as chapters that address new topics such as use of wireless automation and Safety Instrumented Systems. This book also provides an extensive bibliography to related publications and topic-specific information. --